Correlation and path coefficient analyses of phenological traits, yield components and quality traits in wheat - Hamideh Semnaninejad; Ghorban Nourmohammadi; Valiollah Rameeh; Ali Cherati (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT This study was conducted to characterize the phenological traits, yield components and quality traits affecting wheat grain yield. Three wheat genotypes were evaluated during three planting dates (November 20, December 5, and December 20) and at four seeding densities 300, 350, 400 and 450 seeds per m2 for two years. Multivariate analyses were conducted based on the interaction effects of planting date and seeding density (PS), planting date and genotype (PG) and seeding density and genotype (SG) mean values. The results of correlation analysis showed that grain yield was significantly and positively correlated with biomass yield (0.91**), days to spiking (0.81**), days to anthesis (0.83**), and days to maturity (0.57*) for PS; with biomass yield (0.94**), days to spiking (0.87**), days to anthesis (0.75*), and harvest index (0.83**) for PG; with gluten index (0.73**), harvest index (0.68*), and 1000-grain weight for SG. Path analysis revealed that biomass yield for PS and PG, harvest index for PG and SG, and gluten index for SG exhibited the highest positive direct effect. Stepwise regression analysis also revealed important effect of biomass yield, harvest index, and days to maturity for improving grain yield in different agronomical conditions.